Time synchronization for long-chain-type wireless sensor networks. (September 2018) - Chen, Zhenping; Huang, Yourui; Wang, Zheng; Tao, Feng
In view of the requirement on time synchronization for a kind of typical wireless sensor networks with long-chain-type topologies, taking into account the three-dimensional network model currently used by the localization algorithms, one feasible time synchronization algorithm is proposed in this article. Under the three-dimensional topology, nodes in the wireless sensor networks are divided into three kinds: the sensing nodes, the relay nodes, and the measured nodes. By analyzing the distribution characteristics of these three kinds of nodes, with the introduction of the pairwise broadcast synchronization and the series multi-hop synchronization protocol, the estimation of the clock offset and the clock skew of all the nodes in the wireless sensor networks are performed by virtue of the joint maximum likelihood and the least-squares method, thus the time synchronization of the wireless sensor networks with long-chain-type topology is solved. Moreover, the sink node evaluates the network periodically and adjusts the synchronizing cycle based on the difference between the network synchronization error and the given synchronization accuracy. The feasibility and effectiveness of this scheme are analyzed by simulations from the synchronization accuracy, the number of synchronization message, and the synchronizing cycle points of view.